A core–shell metal–organic-framework (MOF)-based smart nanocomposite for efficient NIR/H2O2-responsive photodynamic therapy against hypoxic tumor cells. Issue 13 (20th March 2017) - Cai, Hui-Juan; Shen, Ting-Ting; Zhang, Jian; Shan, Chang-Fu; Jia, Jian-Guo; Li, Xiang; Liu, Wei-Sheng; Tang, Yu
Abstract : In this work, core–shell MOF-based smart nanocomposite UCNPs/MB@ZIF-8@catalase has been constructed for bio-imaging and efficient NIR/H2 O2 -responsive photodynamic therapy against hypoxic tumor cells. Abstract : Core–shell MOF-based smart nanocomposite UCNPs/MB@ZIF-8@catalase (UCNPs = upconversion nanoparticles; MB = methylene blue; ZIF = zeolitic imidazolate framework) has been constructed for bio-imaging and efficient NIR/H2 O2 -responsive photodynamic therapy against hypoxic tumor cells. The nanoporous MOF shell can prevent aggregation of photosensitizers and serve as an efficient self-sufficient oxygen gas acceptor.